2018
DOI: 10.1159/000487136
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic and Environmental Factors of Primary Membranous Nephropathy: An Overview from China

Abstract: Background: Primary membranous nephropathy (pMN) is the most common cause of nephrotic syndrome in adults. The discovery of the 2 autoantigens, M-type phospholipase A2 receptor (PLA2R) and thrombospondin type-1 domain-containing 7A (THSD7A), has defined pMN as an autoimmune disease. A remarkable increase in the frequency of pMN in primary glomerular disease was witnessed in China. The genetic and environmental contributors to disease susceptibility have been investigated in these patients. Summary: We reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 109 publications
1
16
0
Order By: Relevance
“…Inflammation enhances the immunogenicity of autoantigens and affects the antigen processing capacity of APCs, which contributes to the autoimmune response. Undoubtedly, genetic susceptibility influences the development of MN, and other pathogenic factors exert an additive effect in determining whether the genetic potential is manifested [94]. Immunization can be augmented by the unmasking of hidden cryptic epitopes undergoing conformational changes upon exposure to environmental stimuli [95].…”
Section: Disparate Paths To the Same Diseasementioning
confidence: 99%
“…Inflammation enhances the immunogenicity of autoantigens and affects the antigen processing capacity of APCs, which contributes to the autoimmune response. Undoubtedly, genetic susceptibility influences the development of MN, and other pathogenic factors exert an additive effect in determining whether the genetic potential is manifested [94]. Immunization can be augmented by the unmasking of hidden cryptic epitopes undergoing conformational changes upon exposure to environmental stimuli [95].…”
Section: Disparate Paths To the Same Diseasementioning
confidence: 99%
“…The pathogenesis of IMN has been associated with environmental stimuli ( 40 ). The morbidity of MN in China has been gradually increasing, which could be possibly related to the long-term exposure to air pollution.…”
Section: Extrarenal Autoimmune Response Can Cause Imnmentioning
confidence: 99%
“…Another study of Han Chinese patients with PLA2R-associated MN reported a strong association with DRB3*0202 [23*], which probably accounts for the DRB1*0301 signal as they are on the same haplotype. Based on in silico modeling studies, the Beijing group reported on three amino acids in the antigen-binding pocket of the HLA-DR beta1 chain that might help to present PLA2R T cell epitopes to activate the immune response, and the authors have suggested that this confers a genetic susceptibility to environmental factors such as industrial pollution [24]. While these are encouraging observations, the functional studies to document immune cell activation and identification of T cell epitopes have yet to be done.…”
Section: What Have We Learned From Genetics In Mn?mentioning
confidence: 99%
“…A recent increase in the incidence of MN in parts of China has been attributed to environmental air pollution, especially in regions with the highest level of pollution with PM 2.5 particles [25*]. The mechanisms for this are still undefined but gene/environmental interactions and release of pro-inflammatory cytokines have been proposed [24]. Although human PLA2R is most strongly expressed in kidney (and in glomerular podocytes in particular), it is also expressed in lung, placenta, liver and skeletal muscle [26].…”
Section: What Triggers the Loss Of Self-tolerance To Pla2r?mentioning
confidence: 99%